A plastic FeNi-based bulk metallic glass and its deformation behavior. (20th June 2021) - Zhou, Jing; Wang, Qianqian; Zeng, Qiaoshi; Yin, Kuibo; Wang, Anding; Luan, Junhua; Sun, Litao; Shen, Baolong
Abstract: The strength and plasticity of Fe39 Ni39 B12.82 Si2.75 Nb2.3 P4.13 bulk metallic glass (BMG) are improved simultaneously by modulating atomic-scale structure through fluxing treatment. The compression strength increases from 3074 to 4220 MPa, and the plastic strain is enlarged from 10.7 % to more than 50 %. The increased mechanical properties of the fluxed FeNiBSiNbP BMG originate from the optimization of atomic-scale structure. More icosahedral-like clusters (ILCs) and crystal-like clusters (CLCs) are found in this FeNi-based BMG with fluxing treatment, and the ILCs are usually surrounded by CLCs. Furthermore, phase separation and a sandwich-like heterogeneous structure of SB are also observed during deformation, indicating the multiscale deformation mechanism and a stable shear-band evolution. The unique "ILC surrounded by CLCs" structure and phase separation lead to a stable plastic deformation process with strong interactions of multiple shear bands, thereby the improved plasticity and strength. This work provides useful guidelines to develop strong and plastic Fe-based BMGs from a structural aspect.